2015
DOI: 10.1016/j.jpeds.2015.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Serial Free Bisphenol A and Bisphenol A Glucuronide Concentrations in Neonates

Abstract: Objective To determine the balance of metabolism of free bisphenol A (BPA) to the inactive conjugate, BPA glucuronide, in neonates. Study design Free BPA and BPA glucuronide concentrations were measured in 78 urine samples collected between December 2012 and August 2013 from a cohort of 44 healthy full term (≥ 37 weeks’ gestation) neonates at two intervals (3 - 6 days and 7 - 27 days of age). A questionnaire was administered at the time of sample collection. Neonates recruited into the study were born in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…Analysis of urine samples from a cohort of healthy full term (≥37 weeks' gestation) neonates at two intervals of age (3-6 and 7-27 days) shows that only the inactive BPA glucuronide (BPAG), but not the free BPA form, is detected with concentrations ranging from <0.1 µg/L to 11.21 µg/L (median: 0.27 µg/L). These results confirm widespread BPA exposure in healthy full-term neonates, and efficient conjugation of BPA to its readily excretable and biologically inactive BPAG as early as 3 days of age (81). However, some studies suggest that cycling of conjugation/deconjugation maintains low but sustained basal levels of free BPA in the fetus (82).…”
Section: Human Environmental Exposuressupporting
confidence: 52%
“…Analysis of urine samples from a cohort of healthy full term (≥37 weeks' gestation) neonates at two intervals of age (3-6 and 7-27 days) shows that only the inactive BPA glucuronide (BPAG), but not the free BPA form, is detected with concentrations ranging from <0.1 µg/L to 11.21 µg/L (median: 0.27 µg/L). These results confirm widespread BPA exposure in healthy full-term neonates, and efficient conjugation of BPA to its readily excretable and biologically inactive BPAG as early as 3 days of age (81). However, some studies suggest that cycling of conjugation/deconjugation maintains low but sustained basal levels of free BPA in the fetus (82).…”
Section: Human Environmental Exposuressupporting
confidence: 52%
“…Human exposure is nearly universal in developed countries and occurs mainly through contaminated beverages and food 3 . Several studies indicate widespread contamination of fetuses and neonates, leading to the questions as to whether such an EDC can affect development [4][5][6] and whether there is a limit for a safe exposure. Currently, the US Environmental Protection Agency (EPA) "safety level" of BPA is set at 50 μg/kg/d i.e.…”
Section: Introductionmentioning
confidence: 99%
“…15 A growing number of studies have reported urinary concentrations of BPA in children worldwide, ranging in ages from infancy to early adolescence (Table S1, Supplement). [3][4][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Many of these studies have considered the effects of sociodemographic factors, such as parental education and household income, on childhood urinary BPA concentrations, while only a few have explored associations with dietary sources of BPA exposure. 20,21,25 Additional studies are needed to identify other potentially modifiable sources of BPA exposure.…”
Section: Introductionmentioning
confidence: 99%